Answer:
Explanation:
Simplifying
-14 + 1 = rt + -4n
Combine like terms: -14 + 1 = -13
-13 = rt + -4n
Reorder the terms:
-13 = -4n + rt
Solving
-13 = -4n + rt
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '4n' to each side of the equation.
-13 + 4n = -4n + 4n + rt
Combine like terms: -4n + 4n = 0
-13 + 4n = 0 + rt
-13 + 4n = rt
Add '13' to each side of the equation.
-13 + 13 + 4n = 13 + rt
Combine like terms: -13 + 13 = 0
0 + 4n = 13 + rt
4n = 13 + rt
Divide each side by '4'.
n = 3.25 + 0.25rt
Simplifying
n = 3.25 + 0.25rt